Recent Research Advances in Multi-Functional Diallyl Trisulfide (DATS): A Comprehensive Review of Characteristics, Metabolism, Pharmacodynamics, Applications, and Drug Delivery Systems - Wang M; Yu J; Xu H; Xu K; Sohail M; Wang J; Ning H; Zhang J; Yu B (International Journal of Nanomedicine)
Maoru Wang,1,* Jiangping Yu,2,* Hui Xu,3 Kexin Xu,3 Muhammad Sohail,4 Jisheng Wang,1 Hong Ning,2 Jianqiao Zhang,5 Bin Yu2 1Drug Dispensing Department, The Third Hospital of Mianyang, Sichuan Mental Health Center, Mianyang, Sichuan, People’s Republic of China; 2NHC Key Laboratory of Nuclear Technology Medical Transformation (MIANYANG CENTRAL HOSPITAL), Mianyang Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Mianyang, Sichuan, People’s Republic of China; 3School of Pharmacy, Collaborative Innovation Center of Advanced Drug Delivery System and Biotech Drugs in Universities of Shandong, Key Laboratory of Molecular Pharmacology and Drug Evaluation, Yantai University, Yantai, Shandong, People’s Republic of China; 4Key Laboratory of Imaging Diagnosis and Minimally Invasive Intervention Research, Zhejiang Engineering Research Center of Interventional Medicine Engineering and Biotechnology, Key Laboratory of Precision Medicine of Lishui City, Lishui Hospital of Zhejiang University, Lishui, Zhejiang, People’s Republic of China; 5Clinical Trials Research Center, Department of Pharmacy, Binzhou Medical University Affiliated Zibo Central Hospital, Zibo, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin Yu, Email medicine2134@163.com Jianqiao Zhang, Email jaybridge@163.comAbstract: Diallyl trisulfide (DATS) is an organic sulfur compound derived from garlic (Allium sativum L). DATS is characterized by its oily and volatile nature, exhibiting insolubility in water and ethanol, while being miscible with ether. This property enhances its extraction process and expands its applicability across various fields. Recent studies have elucidated the diverse effects of DATS, demonstrating significant progress in healthcare, the food industry, and nanoformulation research. Research on DATS is currently limited, hindering a comprehensive understanding and appreciation of its possibilities for future development. This review offers an in-depth examination of the characteristics of DATS, highlighting the significant advancements and benefits achieved in the fields of drug metabolism, pharmacological effects, clinical trials, food chemistry applications, and nanoformulation research over the past two decades. In addition, this review examines the future prospects of DATS, emphasizing its current development status and challenges, while serving as a crucial reference for advancing research, application, and innovation in the field.Keywords: diallyl trisulfide, DATS, metabolism, pharmacological effects, food applications, clinical treatment, drug delivery systems